A novel inflammasome-related gene nomogram predicts survival in hepatocellular carcinoma. Issue 8 (22nd February 2023) - Lv, Zhengqi; Li, Heng; Yuan, Yiwen; Wu, Qinghua
Abstract : Inflammasomes are closely associated with the progression of multiple cancers. We established an inflammasome-related gene (IRG)-based model to predict the survival of patients with hepatocellular carcinoma (HCC). The RNA-sequencing data and clinical information of HCC patients were downloaded from the cancer genome atlas-liver hepatocellular carcinoma database, and the differentially expressed inflammasome-related gene were screened. Seven prognostic differentially expressed inflammasome-related genes were identified by univariate Cox analysis and incorporated into the risk model using least absolute shrinkage and selection operator-Cox algorithm. The predictive accuracy of the risk model was evaluated through the Kaplan–Meier, receiver operating characteristic and Cox regression analyses. The performance of the model was verified in the International Cancer Genome Consortium-Liver Cancer - RIKEN, JP cohort. A nomogram was constructed to predict the 1-, 2-, 3-, and 5-year survival of HCC patients, and its performance was evaluated using calibration curves. The significantly enriched gene ontology terms, Kyoto encyclopedia of genes and genomes pathways and infiltrating immune cell populations associated with the IRG model were also analyzed to explore of the potential molecular mechanisms and immunotherapeutic targets. An independent and highly accurate prognostic model consisting of 7 IRGs was established and verified in 2 independent HCC cohorts. The IRG model was significantly associated with cell division and cell cycle. In addition, the high-risk group was more likely to have greater infiltration of immune cells and higher expression of immune checkpoint-related genes compared to the low-risk group. An IRG-based model was established to predict 1-, 2-, 3-, and 5-year survival rate in individual HCC patients, which provides new insights into the role of inflammasomes in HCC.